2018
DOI: 10.1108/itp-12-2015-0307
|View full text |Cite
|
Sign up to set email alerts
|

Intention to donate via social network sites (SNSs)

Abstract: Purpose The purpose of this paper is to explore the differences in the external factors influencing intention to donate via social network sites (SNSs), and the online donation knowledge and awareness effect on the willingness to donate via SNS in the future between Malaysian and South Korean users. Design/methodology/approach In total, 288 samples’ data obtained from online survey using the snowball technique were analyzed through using cross-tabulation with χ2 tests and multiple regression analysis. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Third, the results also suggested that MSNS information has significant effects on people's attitude towards donating to a personal medical crowdfunding project. The results for MSNS information are in line with the findings of Ahn et al (2018), which indicated that MSNS information has significant effect on people's overall attitude towards online donation on Malaysian.…”
Section: Structural Modelsupporting
confidence: 83%
See 1 more Smart Citation
“…Third, the results also suggested that MSNS information has significant effects on people's attitude towards donating to a personal medical crowdfunding project. The results for MSNS information are in line with the findings of Ahn et al (2018), which indicated that MSNS information has significant effect on people's overall attitude towards online donation on Malaysian.…”
Section: Structural Modelsupporting
confidence: 83%
“…Therefore, this study is also helpful for future studies to compare the factors influencing the behavioral intentions of potential donors of personal medical crowdfunding in different countries from a cross-cultural perspective. In fact, consumers with different cultural orientations have different donation intentions and behaviors (Gauher et al, 2013;Dean et al, 2018;Ahn et al, 2018).…”
Section: Implication For Theory and Practicementioning
confidence: 99%
“…Finally, the most striking result is that background factors (employment condition and age) are significant but negatively, meaning that young and unemployed persons are more prone to donating to pro-rural initiatives. Firstly, this could be explained by the fact that young people are more often Internet users, therefore they are more familiar with the crowdfunding mechanism and according to [55,56], online fundraising might encourage young donors. Secondly, in some way, the young and unemployed seem to be more concerned with sustainable rural projects (empathy concern positively affects the donation decision, [57]).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, IS researchers have examined various aspects of social networks, such as the ones dealing with security (Ikhalia et al , 2019), ethics (Jones, 2017), fatigue (Malik et al , 2020) and excessive use (Yu et al , 2018). While the academic interest in the research on the intersection of culture and social networks is increasing (Wenninger et al , 2019a; Ahn et al , 2018; Yau et al , 2019; Hu et al , 2020), there are several “unique opportunities and contextualized benefits in conducting cross-cultural analysis in SNS [social network services]” (Guo et al , 2020, p. 3). Moreover, the research advancing the role of cultural factors has become increasingly salient in recent years as social networks, “continue to bring our nations and cultures together, and as individuals increasingly move across the cultural landscape as national borders diminish in importance” (Warkentin et al , 2015, p. 233).…”
Section: Discussionmentioning
confidence: 99%